Educação de jovens e adultos: uma parceria entre o Estado e a sociedade organizada - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2006)
This work has as focus the analysis of partnership betwen the Ponta Grossa city hall andd Integrar Institute for the construction of a formation way directed to Youthful and Adult. Searched how occured the union between the State represented by Secretaryship of Education and the organized civil society represented by a organization of the third sector non profit making raised by Central Única dos Trabalhadores. Used the materialist dialetic as the method of investigation which claimed a straight connection with the real reality and a historical analysis of social and economy Brazilian situation that created the condition necessaries to appearing of this Program, acknowledge the main transformation happened in the State, in the labor market, in the civil society and on the Education of Youthful and Adult, as well the growth of the “third sector”. This work show that factors as the neoliberalism and the globalization of economy changed the size and the paper of Brazilian State as well as the way how it passed to dialogue with the civil society beyond to make labor market and to calim the articulation among the social and economic interest first things first of politics of EJA. With this investigated process could to understand how a group of a Municipal district engaged with workers accomplish a partnership with a Program commitment with the social transformation and as the students attended by this Program evaluate its. On the study searched to understand how this social phenomenon, important to the Sindical Moviment and to the formulated of Politics os EJA, appear and develop and what is the comprehension that the workers have about this experience.
Keywords: Política Educacional; educação de jovens e adultos; mercado de trabalho; transformação social; Politics Education; education of youthful and adult; labor market; social transformation; CNPQ::CIENCIAS HUMANAS::EDUCACAO